Zoroastrianism's view of women - Saeed, Prof. Dr. Emad Abdelkader Mohamed (Sulaimani Journal for Humanities, 2026)
The Zoroastrian religion is among the most important religions found in Kurdistan and ancient Iran. This religion has dealt with many topics related to society, including those related to women, as women are mentioned in many Astrian texts. Where she played the role of a senior female in Zoroastrian society. So, a man is a woman is normal. For this reason, we had to study the Zoroastrian religion of women. This research has been divided into two parts. The first research mentioned the possibility of the emergence of the Zoroastrian religion. The second topic relates to the status of women in this religion. This is done by knowing her place in society. Also, knowledge of women’s rights on issues (marriage , adoption , inheritance , right to education).